Synthesis and characterization of phosphorus-containing methacrylate-based difunctional crosslinkers and their use in UV-curable resin systems - Inan, TY; Özarslan, Ö; Kuyulu, A; Ekinci, E; Güngör, A (JOHN WILEY & SONS INC, 1999)
Two new phosphorus-containing methacrylate-based difunctional crosslinking agents [bis(4-(2-methacryloyloxy)ethyl carboxyl)phenyl phosphine oxide (BEPPPO) and bis(4-(2-methacryloyloxy)ethylcarbonylaminophenyl)phenyl phosphine oxide (BUPPPO)], which can be good candidates for W-curable coating applications, were synthesized by reacting either a phosphorus-containing diisocyanate [bis(4-isocyanatophenyl)phenyl phosphine oxide] or a phosphorus-containing diacid chloride [bis(4-chloroformylphenyl)phenyl phosphine oxide] with hydroxyethyl methacrylate. The structures of the monomers thus obtained were characterized by FTIR, mass, and H-1-NMR spectroscopies. The contents of the new crosslinking agents in the UV-cured polymeric films were varied between 10 and 30% by weight. Mechanical, physical, and thermal characterizations of the W-cured films were investigated. An increase in crosslinking agent content caused an increse in mechanical properties. Films containing BUPPPO had higher tensile strength values compared to the films containing BEPPPO. Thermogravimetric analysis of phosphorus-containing crosslinking agents revealed that incorporating phosphorus into the structure resulted in a high char yield up to 24.5% at 600 degrees C. Water absorption values of UV-cured films were also affected by the amount and type of crosslinking agent. (C) 1999 John Wiley & Sons, Inc.
Keywords: UV curable; phosphorus; methacrylate; crosslinking agents; URETHANE; Polymer Science